MULTIMODAL TREATMENT WITH HYPNOSIS IN THE DEPRESSIVE STATE IN ADJUSTMENT DISORDERS - Águila-Castillo, Daniel (2022)
Hypnosis is a medical procedure that has accompanied man since primitive stages, and in the last 50 years its study and practice has gained more space within the field of Psychology. In the Psychiatry service of the Manuel Fajardo Rivero Hospital, Villa Clara, Cuba different diseases are treated through the use of this technique. Taking into account the results achieved in emotional disorders and the high incidence of adjustment disorders, where depression is one of the most frequent clinical syndromes, this research was aimed at conducting an explanatory study with a quantitative approach, with the objective of evaluating the effectiveness of multimodal treatment with hypnosis in the attenuation of the depressive state in adjustment disorders, in the period from January to October 2017. The sample was selected in a non-probabilistic, intentional way, being made up of 20 patients, in ages between 18 and 35 years old. Documentary review, clinical interview, Beck's inventory and the depression evaluation scale by specialists were used. The patients evaluated presented before starting the multimodal treatment a depressive state with a predominance of thought and somatic symptoms. After treatment, the initial depressive state was not confirmed. The main manifestations that formed a depressive state before starting treatment were greater in intensity and frequency than those present at the end of it, not presenting indicators of depressive nosological identity.